Rasio Neutrofil Limfosit Sebagai Prediktor Tingkat Keparahan Stroke Iskemik - Thaharatin Giza Wulandari (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2019)
Among the several types of strokes, ischemic stroke has the highest incidence of about 80% to 85% and is characterized by a disruption in blood flow in the brain. There are many inflammatory markers identified as possible predictors of prognosis in ischemic stroke. Compared to other inflammatory markers, leukocyte counts are the most widely used and simplest. Neutrophils and lymphocytes are the main components in leukocytes. The neutrophil lymphocyte ratio has been proposed as an easy parameter to assess a person's inflammatory status. The neutrophil lymphocyte ratio can reflect an imbalance between overactive inflammation and protective reagulation and has advantages over using neutrophils or lymphocytes alone. The neutrophil lymphocyte ratio is easy to obtain, noninvasive, and one of the inexpensive markers of inflammation, and can be used routinely to indicate the status of systematic inflammation in clinical work.